Autoimmune pancerebellitis as an immune-related adverse event: an illustrative case - D. Valančius; I. Zagorskienė; A. Klimašauskienė (Neurologijos seminarai)
Immune checkpoint inhibitors have already proved their effectiveness in the treatment of various forms of cancer, and every day their use is becoming more and more prevalent. Unfortunately, every effective treatment has its side effects, and immunotherapy is no exception. In this article, the authors present an illustrative and rare clinical case of a patient who developed autoimmune pancerebellitis during therapy with immune checkpoint inhibitors.